Surgical Treatment of Fibroosseous Lesion in Young Patient with Reduced Mouth Opening - Azambuja Carvalho, Pedro Henrique de [UNESP]; Torriani, Marcos Antonio; Post, Leticia Kirst; Chagas Junior, Otacilio Luiz (Thieme Medical Publ Inc, 2018)
Fibrous dysplasia is a benign fibroosseous disorder that can affect the maxillary bones, causing aesthetic deformity and functional impairment. This article reports the case of a 13-year-old male patient at the time of diagnosis. The patient showed increased facial volume with relevant asymmetry, having reported the onset of the condition 12 months before. Upon examination, the patient presented an 8-mm mouth opening and an acute inflammatory process associated with tooth 37 pericoronal hood. Upon imaging exam, exuberant bone growth in the left mandibular ramus area of ground glass aspect was observed. After incisional biopsy, fibrous dysplasia was diagnosed and sequentially treated with osteoplasty and coronoid process removal. The patient evolved to a 43-mm mouth opening and favorable aesthetics without recurrence in a 3-year follow-up period. In this case, coronoidectomy and bone plasty proved to be effective, returning aesthetics and function. The patient is supposed to be followed up in the long term.
Keywords: fibrous dysplasia; functional impairment; surgical treatment; case report